2015
DOI: 10.20533/ijcdse.2042.6364.2015.0289
|View full text |Cite
|
Sign up to set email alerts
|

How to Design Empowering Work-based Learning Settings to Foster Students’ Competence Development

Abstract: Equipping students with competences which enhance employability is a central aim of higher education that can be reached through work-based learning (WBL) settings. However, the research in higher education on individual and contextual enabling factors of WBL settings is still fragmented. In order to contribute to a systematic design approach, we widen the higher education perspective towards organisational studies, especially the construct of "empowerment". This approach systematically captures the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Predating graduate apprenticeships, employers and HEIs have a long history of collaboration on work-based learning courses that create workplace learning opportunities (Boud and Solomon 2001) and acknowledge this by means of academic credit (Feldmann and Sprafke 2015;Mulkeen et al 2017). Curriculum development in these contexts has previously been, in the main, the domain of HEIs (Hordern 2014).…”
Section: Models For Degree Apprenticeshipsmentioning
confidence: 99%
“…Predating graduate apprenticeships, employers and HEIs have a long history of collaboration on work-based learning courses that create workplace learning opportunities (Boud and Solomon 2001) and acknowledge this by means of academic credit (Feldmann and Sprafke 2015;Mulkeen et al 2017). Curriculum development in these contexts has previously been, in the main, the domain of HEIs (Hordern 2014).…”
Section: Models For Degree Apprenticeshipsmentioning
confidence: 99%
“…The literature on Employability skills concerns to emotional intelligence, selfefficiency and personal attributes among graduates shows skills deficiency (Tran, 2016;Feldmann, 2015;Jackson, 2015;Rateau et al, 2011;Pillai, 2009;Dacre Pool & Sewell, 2007;Knight & Yorke, 2003;Jain & Jain, 2013;Nauta et al, 2009;Brown et al, 2006;Finch et al, 2015;Dacre Pool & Qualter, 2012;Kirk et al, 2008). Dacre Pool et al 2014state that very few models in previous research studies tested broad concepts of employability among graduates for job readiness, researchers recommend the need to include theme in the model.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of interest in a topic typically lead to increased exposure, enhanced learning, and subsequent engagement with that topic [56][57][58][59]. Interest and self-efficacy are associated and, together, they shape an individual's future goals [60][61][62]. Social cognitive career theory (SCCT) research has shown that math and science attitudes (e.g., self-efficacy, anxiety, and outcomes expectations) are predictive of students' level of interest in science, generally, and students with higher levels of science interest are more likely to select and persist in science majors [62,63].…”
Section: Math Attitudes and Geoscience Interestmentioning
confidence: 99%